Aster leafminer moth Leucospilapteryx venustella (Clemens) (Insecta: Lepidoptera: Gracillariidae) - Rodrigo Diaz; Esteban Tapia; Veronica Manrique; William Overholt; Donald Davis (EDIS, 2014)
Leucospilapteryx venustella (Clemens) (Lepidoptera: Gracillariidae) is a small, mostly light brown moth that, during its larval stages, creates mines in the leaves of plants in the family Asteraceae. Feeding damage by the early instars is characterized by serpentine mines that are expanded by later instars to form tentiform or blotch mines. This 4-page fact sheet was written by Rodrigo Diaz, Esteban Tapia, Veronica Manrique, William Overholt, and Donald Davis, and published by the UF Department of Entomology and Nematology, February 2014.